Long-term results of inferior turbinate reduction with argon plasma coagulation - Bergler, Wolfgang; Sadick, Haneen; Hammerschmitt, Nicolas; Oulmi-Kagermann, Jasmina; Hörmann, Karl (The laryngoscope, 2001)
Objectives Surgical reduction of the inferior turbinates is a commonly used therapy in patients with hyperplastic inferior turbinates when medical management remains ineffective. Current surgical methods have disadvantages (e.g., necessity of nasal packing, extended postoperative swelling, and high costs). Theoretical considerations render argon plasma coagulation (APC) a promising new therapeutic approach. Study Design In a prospective study, 121 patients with chronic nasal obstruction were treated for inferior turbinate reduction with APC. Hyperplasia of the nasal turbinates was diagnosed rhinoscopically and endoscopically and confirmed rhinomanometrically. The mean follow-up period was 12 months, ranging from 10 to 16 months. The treatment results were evaluated by a questionnaire, rhinomanometric findings, and electron microscopic studies of the nasal mucosa. In 50 patients a ciliary function test was performed preoperatively and postoperatively. Methods Argon plasma coagulation, a high-frequency electrosurgery, has been used for volume reduction of the inferior turbinate in local anesthesia. Results Seventy-six percent of the patients reported an improvement of the postoperative swelling within the first week. After 6 weeks, macroscopically the turbinates were re-epithelialized by normal mucosa in 63% of the patients. Electron microscopic studies after 3 months verified normal cilia. After 12 months, 83% of the patients stated that they had a better nasal airflow than preoperatively. Crust formation was minimal. No bleeding or impaired ciliary function occurred. Ninety-five percent of the patients were willing to undergo the same operation again. Conclusion The long-term results have proved APC to be an effective and easy-to-perform alternative for inferior turbinate reduction with comparable results to other established surgical methods.
Presented at the Meeting of the 18th Congress of the European Rhinologic Society, Barcelona, Spain, June 29, 2000
Elektronische Reproduktion der Druckausgabe
Gesehen am 06.05.2022
Keywords: Konferenzschrift